KARAKTERISTIK PERTUMBUHAN JARAK PAGAR (Jatropha curcas L.) YANG DITAMBAHKAN CENDAWAN ENDOFIT PADA LAHAN PASCA TAMBANG TIMAH - Sukmarayu P. Gedoan; Alex Hartana; Hamim Hamim; Utut Widyastuti; Nampiah Sukarno (Graduate School Bogor Agricultural University (SPs IPB), 2013)
Tin mining activity caused canging in physical and chemical characteristic of the soil that were not suitable for growth of plants. The objective of this experiment was to study accessions of Jatropha curcas planted on post tin mining land which were given endophyte. This research was conducted in a Sinar Baru village TS 133, district of Bangka, Bangka Belitung province for field research conducted in May 2007 to April 2008. The experimentas a factorial experiment in the design of the randomized complete block design with three replications. The main plot is 7 accessions consisting of: accession Madiun, Ponorogo, Jember, Dompu, Lampung, Bengkulu, andSukabumi, while the subplot of the land without giving endophyte fungal (control) and the provision of endophyte fungal in baglog 250 g. Each experimental unit contained four plants per plot.The result showed that vegetative growth the highest for the former tin mining land given endophyte fungal vary in some accessions. Accession to the highest Sukabumi: plant height, branch number, plant dry weight, dry weight of the shoot, and root dry weight, the largest diameter have Jember accession, accession Dompu had the highest canopy diameter, and the accession of Lampung has the lowest ratio of shoot roots.Keywords: Jatropha curcas, accession, fungal endophyte